2021
DOI: 10.2989/10220119.2021.1918247
|View full text |Cite
|
Sign up to set email alerts
|

Biogeographical patterns of grasses (Poaceae) indigenous to South Africa, Lesotho and Eswatini

Abstract: The grass family, Poaceae (Gramineae) is considered the most valuable plant family in food production worldwide. In addition to its importance as a grain crop (e.g. maize, wheat and rice), its tolerance to grazing, fire and drought, makes grasses a significant component of livestock feed, mainly sourced from rangeland and/or planted pastures. Soreng et al. (2017) recognised at least 11 506 grass species worldwide of which approximately 685 species are indigenous to southern Africa (Trytsman et al. 2020).Consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 46 publications
1
5
0
Order By: Relevance
“…The Poaceae family was found to be the most important botanical family with 94.7% (n = 18) useful invasive grass species, whereas Juncaceae contains only 5.3% (n = 1) rush species. High species richness within the family Poaceae demonstrates species diversity within this family [48,[69][70][71][72][73]. The findings of this review are not unique, but serve as confirmation of similar findings in studies done by Schubert et al [74] and Díaz and Jorquera [75].…”
Section: Taxonomic Nomenclature and Origin Of Speciessupporting
confidence: 88%
“…The Poaceae family was found to be the most important botanical family with 94.7% (n = 18) useful invasive grass species, whereas Juncaceae contains only 5.3% (n = 1) rush species. High species richness within the family Poaceae demonstrates species diversity within this family [48,[69][70][71][72][73]. The findings of this review are not unique, but serve as confirmation of similar findings in studies done by Schubert et al [74] and Díaz and Jorquera [75].…”
Section: Taxonomic Nomenclature and Origin Of Speciessupporting
confidence: 88%
“…The statistical software PC-Ord, version 5.31 [26] was used to perform the cluster analysis, applying the Euclidean distance for dissimilarity and Ward's linkage. Previous studies with southern African grasses and legumes showed that, although PC-Ord formed disjointed groups, it was more accurate in placing QDGCs in the resulting phytochoria compared to using XLSTAT 1 Jun 2010 Software (Addinsoft to MS Excel) [24]. The geographical distribution of the clusters resulting from the AHC was compared with existing maps of well supported phytogeographical regions in the study area, especially those depicting biomes and bioregions [27] of southern Africa.…”
Section: Methodsmentioning
confidence: 99%
“…The QDGCs assigned to ecotones (where two or more biomes or bioregions converge in a QDGC) were not included in the dataset where the key biomes and bioregions of browse-choria are defined. Similar to previous studies [22,24], the total number of occurrences (records) in a browse-chorion was calculated, and 20 key species with the highest occurrences were selected to identify species with presumably wide ecological tolerance in a particular browse-chorion. The collection intensity (expressed as the number of browsed species per QDGC collected as herbarium specimens) was calculated and mapped on the biome and bioregion maps of South Africa, Lesotho, and Eswatini [28].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations